Ameliorative effect of Naja haje venom against arthritic influence of Freund's complete adjuvant FCA in paw and ankle of male rats - Nabil A. Soliman; Amr A. Shalaby; Mayada R. Farag; Shimaa Kamal; Sara M. Abdelkarem Alashqar; Mohamed Ahmed Ammar; Suzan Attia Mawed (Open Veterinary Journal)
Background: Pain and inflammation are closely associated with rheumatoid arthritis (RA), which affects the bones and joints.